Grammatical Awareness: Its Relationship to the Writing Proficiency of Grade 12 Learners - Varas, Marc Arvee (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between grammatical awareness and writing proficiency among Grade 12 learners in selected private schools in Agoo, La Union during the School Year 2025–2026. Anchored on theories such as Skill Acquisition Theory, Metalinguistic Awareness Theory, Communicative Language Teaching, and Process Writing Theory, the study investigated learners’ grammatical awareness, the seriousness of grammar-related difficulties, the effectiveness of teachers’ instructional strategies, and the learners’ writing proficiency. A descriptive-correlational research design was employed using a validated researcher-made questionnaire administered to Grade 12 learners and English teachers. Frequency counts, weighted mean, and Pearson Product-Moment Correlation Coefficient were utilized in analyzing the gathered data. The findings revealed that learners generally demonstrated a high level of grammatical awareness, particularly in sentence construction, article usage, and proper use of conjunctions and prepositions. However, learners encountered moderately serious difficulties in maintaining tense consistency, applying grammar spontaneously, and identifying sentence structure errors. Teachers’ instructional strategies were perceived as effective, especially the use of assessment, explicit instruction, and technology-assisted grammar activities. Despite these positive findings, learners’ writing proficiency remained moderate, particularly in macro-structural organization, cohesion, and sustained grammatical accuracy. The study further established a statistically significant relationship between grammatical awareness and writing proficiency, indicating that learners with stronger grammatical awareness tend to demonstrate better writing performance. The study supports SDG 4: Quality Education by promoting effective grammar instruction and writing development to strengthen learners’ academic competence and communication skills. It also relates to SDG 8: Decent Work and Economic Growth through the enhancement of language competencies necessary for higher education and future employment. The findings contribute to educational sustainability by providing evidence-based intervention strategies that may improve grammar instruction, writing proficiency, and curriculum implementation in English language education.
Keywords: Academic Writing; English Grammar; Grammatical Awareness; Instructional Strategies; Writing Proficiency; Writing Skills